Comparison of Antifungal Activity of 2% Chlorhexidine, Calcium Hydroxide, and Nanosilver gels against Candida Albicans. - Mohammad Ali Mozayeni; Ali Hadian; Pedram Bakhshaei; Omid Dianat (Tehran University of Medical Sciences, 2015)
Residual microorganisms in the root canal system (RCS) after endodontic therapy such as Candida albicans are a major cause of endodontic failure. Calcium hydroxide (CH) and chlorhexidine (CHX) have suitable antimicrobial activity against bacteria and can be used as intracanal medicaments. Nanosilver has also shown antimicrobial activity against microorganisms. This study aimed to compare the antifungal effect of calcium hydroxide, 2% chlorhexidine and nanosilver gels on Candida albicans.Eighty-one single-rooted teeth were selected. After root canal preparation, the teeth were contaminated. After culture, the teeth were randomly divided into 4 groups. In experimental groups, 24 teeth were selected and completely filled with CH, 2% CHX and nanosilver gels in each group. Nine teeth were selected in the control group and filled with saline solution. After 1, 3, and 7 days, samples were obtained by #30 sterile paper points, and #2 and #4 Gates Glidden drills and cultured on solid Sabouraud agar.The results demonstrated that CH and 2% CHX had equal antifungal effects on samples taken by paper point and #2 Gates Glidden drill at all time points. Both CH and 2% CHX were more effective than nanosilver at all time periods. There was no statistically significant difference between medicaments in samples taken by #4 Gates Glidden drill.CH and 2% CHX gels have significantly higher antifungal activity than nanosilver gel. Also, CH and 2% CHX gels are equally effective against Candida albicans.